2006
DOI: 10.1063/1.2336197
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between thermodynamics and dynamics of supercooled liquids

Abstract: Diffusivity, a measure for how rapidly a fluid self-mixes, shows an intimate, but seemingly fragmented, connection to thermodynamics. On one hand, the "configurational" contribution to entropy (related to the number of mechanically-stable configurations that fluid molecules can adopt) has long been considered key for predicting supercooled liquid dynamics near the glass transition. On the other hand, the excess entropy (relative to ideal gas) provides a robust scaling for the diffusivity of fluids above the fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 24 publications
4
41
0
Order By: Relevance
“…The excess entropy S 2 describes the contribution of two-point correlations to the total entropy of the system. It has been found that S 2 agrees very well with the total entropy in different systems including some models of water (43,44).…”
Section: Relation Of Tetrahedral Entropy To Translational Order Paramsupporting
confidence: 64%
“…The excess entropy S 2 describes the contribution of two-point correlations to the total entropy of the system. It has been found that S 2 agrees very well with the total entropy in different systems including some models of water (43,44).…”
Section: Relation Of Tetrahedral Entropy To Translational Order Paramsupporting
confidence: 64%
“…Interestingly, this was suggested by Bestul and Chang 96 in a paper preceding Adam-Gibbs by one year, which showed data consistent with a universal value of the excess entropy at the glass transition for several liquids. Much more recently, Truskett and co-workers 97 suggested that the excess entropy S ex controls the relaxation time in the spirit of Rosenfeld 76,77 scaling; this is also consistent with isomorph invariance. As a final example of a theory where entropy controls the relaxation time, consider the random first-order transition ͑RFOT͒ theory of Wolynes and co-worker ͑reviewed in Ref.…”
Section: Cause Of the Non-arrhenius Relaxation Time: The "Isomorph Fimentioning
confidence: 61%
“…Deviations from this linear relation were already reported in supercooled liquids 38,65,66 , alkanes at high densities 37 and water 39,42 . In this work, we use a third order polynomial, where the second and third order terms account for deviations from the linear behaviour that we found when applying Eqs.…”
Section: Viscosity Based On Group Contributionsmentioning
confidence: 75%